The contribution of knowledge communication in mangrove rehabilitation projects in Cadiz City, Negros Occidental. - Delariarte, Ana Raffaela I.; Razonable, Christian Leigh G. (2016.)
Mangroves are very important to the Philippine ecosystem. For the past years though, mangrove rehabilitation projects initiated in the country have had low success rates. Today, there are Community-based Mangrove Rehabilitation Projects (CMRPs) as a post-Yolanda effort to help local communities within the coastal area. It is initiated by the government and the members of the local community are the active participants of the project. These projects tap local people?s organizations and train them of the proper planting and maintenance of mangroves. Members of people?s organization then have the responsibility of planting and tending the mangroves to ensure high survival rates. Members from government implementing agencies conduct the trainings and communicate with the local communities from time to time to check up on the mangroves. This paper examines how communication plays a role in the mechanism between government implementers and people?s organizations in the implementation of mangrove projects in 5 communities in Cadiz City, Negros Occidental. This paper will look into the kind of communication that transpires between those involved in CMRP, how the process of communication takes place and how it affects the engagement among members of people?s organizations and how the process of communication from experts to common people contribute to the success or failure of this mangrove projects. Key informant interviews were conducted with representatives from Local Government Unit (LGU), Provincial Environment Management Office (PEMO), Department of Environment and Natural Resources (DENR) and Bureau of Fisheries and Aquatic Resources (BFAR), all of which are government implementing agencies that are involved in mangrove-related projects. Focus group discussions (FGDs) were also conducted in five barangays and their corresponding people?s organizations. Content analysis of pamphlets used by government implementing agencies for training, and tarpaulins and posters given to the local community was also done. The results of the study show that the flow of communication is structured and organized within the actors having specific roles. Corresponding Hiligaynon (local language) terms for the species of mangroves also aided in the understanding of the technicalities in planting and maintenance of mangroves. Coastal communities accept their role as environment stewards and recognize their role as stakeholders. It is also because of this that they become more cognisant of the ecological importance of mangroves. They recognize its function in helping them keep safe during typhoons or from big waves, and also as a breeding ground of fishes. Communities are passive recipients of expert knowledge from LGU implementing agencies; they do not articulate, insist or contest using their own local knowledge CMRP.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Mangrove Rehabilitation -- Cadiz City, Negros Occidental; Mangroves; Community-based Mangrove Rehabilitation Projects (CMRPs)